Cholangiocarcinoma in a Child with Progressive Abdominal Distension and Secondary Hypercalcemia - Chalinee Monsereenusorn; Kantang Satayasoontorn; Piya Rujkijyanont; Chanchai Traivaree (Case Reports in Pediatrics)
Cholangiocarcinoma is extremely rare in childhood and has been reported in association with other underlying diseases. The survival and prognosis are dismal especially in patients with unresectable or advanced stage cholangiocarcinoma. Overall survival in patients with metastatic cholangiocarcinoma could be increased by using combination chemotherapy with cisplatin and gemcitabine. A case of childhood cholangiocarcinoma was hereby reported.